The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5829/ijee.2018.09.02.05
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Detailed Analysis for a Proposed 5kW PV Grid-Connected System Installed in Iraq Using PVsyst Tool

Abstract: In this study, PVsyst simulation software is used to analyze a PV grid tied system in a typical primary school in Iraq. The proposed system is 5kW which is affordable and applicable from the cost and required area points respectively. The monthly averaged electrical load for a typical school is approximately calculated. The system simulation has been done for thirteen Iraqi provinces while it is described and its performance is analyzed in details for Baghdad city as an example. The performance ratio for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They have concluded that the PV system is a feasible and viable choice to supply the present and future electricity demand. Many Iraqi and foreign researchers studied the performance design of solar PV systems using on-grid connection technology [20][21][22][23][24][25]. Korsavi et al studied the 5kW rooftop solar PV system in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that the PV system is a feasible and viable choice to supply the present and future electricity demand. Many Iraqi and foreign researchers studied the performance design of solar PV systems using on-grid connection technology [20][21][22][23][24][25]. Korsavi et al studied the 5kW rooftop solar PV system in Iran.…”
Section: Introductionmentioning
confidence: 99%